PROGRESS IN PIG-TO-NONHUMAN PRIMATE TRANSPLANTATION MODELS (1998–2013): A COMPREHENSIVE REVIEW OF THE LITERATURE - Cooper, David K.C. (2014)
The pig-to-nonhuman primate model is the standard choice for in vivo studies of organ and cell xenotransplantation. In 1998 Lambrigts and his colleagues surveyed the entire world literature and reported all experimental studies in this model. With the increasing number of genetically-engineered pigs that have become available during the past few years, this model is being utilized ever more frequently. We have now reviewed the literature again and have compiled the data we have been able to find for the period January 1(st) 1998 to December 31(st) 2013, a period of 16 years. The data are presented for transplants of the heart (heterotopic and orthotopic), kidney, liver, lung, islets, neuronal cells, hepatocytes, corneas, artery patches, and skin. Heart, kidney, and, particularly, islet xenograft survival have increased significantly since 1998, and the reasons for this are briefly discussed. A comment on the limitations of the model has been made, particularly with regard to these will affect progression of xenotransplantation towards the clinic.